2001
DOI: 10.1021/om010235z
|View full text |Cite
|
Sign up to set email alerts
|

Syntheses and Structures of New Luminescent Cyclometalated Palladium(II) and Platinum(II) Complexes:  M(Bab)Cl, M(Br−Bab)Cl (M = Pd(II), Pt(II)), and Pd3Cl4(Tab)2 (Bab = 1,3-bis(7-azaindolyl)phenyl, Br−Bab = 1-Bromo-3,5-bis(7-azaindolyl)phenyl, Tab =1,3,5-tris(7-azaindolyl)phenyl)

Abstract: The reactions of blue luminescent ligands 1,3-bis(7-azaindolyl)benzene (BabH), 1-bromo-3,5-bis(7-azaindolyl)benzene (Br-BabH), and 1,3,5-tris(7-azaindolyl)benzene (TabH) with K 2 PdCl 4 and K 2 PtCl 4 have been investigated. Five new luminescent cyclometalated palladium(II) and platinum(II) complexes Pd(Bab)Cl (1), Pt(Bab)Cl (2), Pd(Br-Bab)Cl (3), Pt-(Br-Bab)Cl (4), and Pd 3 Cl 4 (Tab) 2 ( 5) have been synthesized and fully characterized. The molecular structures of 1 and 2, and 3 and 4, are similar. There are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
31
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(36 citation statements)
references
References 10 publications
5
31
0
Order By: Relevance
“…[9] By replacing the pyridine rings with azaindoles in the N^C^N ligand, the complexes only emit in low-temperature glass in spite of the relief of angle strain. [10] Recently, our group has reported a new class of luminescent cyclometalated platinum(II) complexes with 2,6-bis(Nalkylbenzimidazol-2'-yl)benzene (bzimb) as the N^C^N ligand and demonstrated that they show green electrophosphorescence in multilayer phosphorescent organic lightemitting devices (PHOLEDs) with a high current efficiency and an external quantum efficiency (EQE) of 38.9 cd A À1 and 11.5 %, respectively. [11a] Although these complexes are unique in that they give rise to intense green phosphorescence, [11] it is envisaged that the utilization of various types of cyclometalated N^C^N ligands with slightly different electronic properties could lead to a gradual variation in the frontier molecular orbital energies to give tunable emission colors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[9] By replacing the pyridine rings with azaindoles in the N^C^N ligand, the complexes only emit in low-temperature glass in spite of the relief of angle strain. [10] Recently, our group has reported a new class of luminescent cyclometalated platinum(II) complexes with 2,6-bis(Nalkylbenzimidazol-2'-yl)benzene (bzimb) as the N^C^N ligand and demonstrated that they show green electrophosphorescence in multilayer phosphorescent organic lightemitting devices (PHOLEDs) with a high current efficiency and an external quantum efficiency (EQE) of 38.9 cd A À1 and 11.5 %, respectively. [11a] Although these complexes are unique in that they give rise to intense green phosphorescence, [11] it is envisaged that the utilization of various types of cyclometalated N^C^N ligands with slightly different electronic properties could lead to a gradual variation in the frontier molecular orbital energies to give tunable emission colors.…”
Section: Introductionmentioning
confidence: 99%
“…A class of pincer platinum(II) complexes of 5‐methyl‐1,3‐bis(benzothiazol‐2‐yl)benzene (bzthb) that shows yellow phosphorescence in solution has also been reported 9. By replacing the pyridine rings with azaindoles in the N^C^N ligand, the complexes only emit in low‐temperature glass in spite of the relief of angle strain 10…”
Section: Introductionmentioning
confidence: 99%
“…The potential of this polydentate ligands to act as C,N,S-pincer ligand after orthometallation reaction with Pd(II) and Pt(II) has also been demonstrated. In a forthcoming paper we will report on the reactivity of these pincer complexes towards insertion reactions of unsaturated organic molecules [12,13], their electronic structures and their photophysical properties [14][15][16][17][18][19][20][21][22]. …”
mentioning
confidence: 99%
“…Similar torsion angles are observed for the monoclinic (Bowes et al, 2005) and orthorhombic forms (Bessel et al, 1992) of 2,2 H :6 H ,2 HH -terpyridine (tpy) and 2,6-bis(5,6,7,8-tetrahydroquinol-2-yl)pyridine (the torsion angles about the C quinolyl ÐC pyridine bond are À168.5 and 165.7 ; Sasaki et al, 1998). On the other hand, 1,3bis(7-azaindolyl)benzene (bab; Wu et al, 2001) and 1-bromo-3,5-bis(7-azaindolyl)benzene (babBr; Song et al, 2001) crystallize with noncoplanar azaindolyl rings, giving rise to a curved conformation (the torsion angles about the N azaindolyl Ð C benzene bonds are in the 20±45 range).…”
Section: Commentmentioning
confidence: 99%